2018
DOI: 10.17576/jsm-2018-4707-21
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Food Utensils Hygiene amongst Food Handlers in Kuala Pilah, Negeri Sembilan, Malaysia

Abstract: This study aimed to evaluate the level of knowledge, attitude and practice (KAP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…The increased number of cases of foodborne disease reflects that this is a public health problem that warrants the need to decrease the number of cases through a better awareness of food hygiene. The emphasis is on the need for improving knowledge, attitude, and the practice of home-based food handlers in food safety as a notable way to minimize the impact of foodborne disease [11].…”
Section: Introductionmentioning
confidence: 99%
“…The increased number of cases of foodborne disease reflects that this is a public health problem that warrants the need to decrease the number of cases through a better awareness of food hygiene. The emphasis is on the need for improving knowledge, attitude, and the practice of home-based food handlers in food safety as a notable way to minimize the impact of foodborne disease [11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when it comes to customer awareness of food poisoning avoidance, the present survey found that most people understand cross-contamination because they use different towels to clean tables and plates and different chopping boards to cut other raw foods. To avoid cross-contamination, a previous study Saipullizan et al (2018) conducted in the rural area of Kuala Pilah, Malaysia, reported that different clothes must be used to clean tables and food utensils, as well as different chopping boards.…”
Section: Discussionmentioning
confidence: 99%
“…Not only actions, knowledge can also indirectly influence the cleanliness of cutlery. Knowledge about the cleanliness of eating/cooking utensils can influence the presence of bacteria on eating/cooking utensils (14).…”
Section: Knowledge and Attitude A Knowledgementioning
confidence: 99%